Demographic transition and the real exchange rate in Australia: An empirical investigation - Hassan, K.; Salim, Ruhul; Bloch, Harry (Routledge, 2015)
This article utilizes the empirical findings that age structure of the population affects saving, investment and capital flow and hypothesizes that age structure influences the real exchange rate. Based on this link, an empirical model is specified for Australia and estimated with annual data for the period 1970–2011. An autoregressive distributed lag model of cointegration indicates that Australia's real exchange rate is cointegrated with its productivity differential and the relative share of young dependents (0–14 years) in the population. Long-run estimates show that young cohort has an appreciating influence on the real exchange rate. Also, the short-run adjustment is substantial, with more than 65% of the disequilibrium corrected in a year.